2014
DOI: 10.4162/nrp.2014.8.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic effect of aqueous extract ofSesamum indicumseeds on ethanol-induced toxicity in male rats

Abstract: The liver is vulnerable to alcohol-related injury because it is the primary site of alcohol metabolism. Additionally, a number of potentially dangerous by-products are generated as alcohol is broken down in the liver. However, dietary supplements may prevent or relieve some of alcohol's deleterious effects. Therefore, this study was conducted to evaluate the prophylactic effect of aqueous extract of Sesamum indicum (SI) on ethanol induced toxicity in rats. Male Wistar albino rats were divided into control, eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Sesame seed is not only a good source of edible nutrients, but is also widely considered to have medicinal value that includes antioxidant, anti-ageing, antimutagenic, antihypertensive, and anti-inflammatory activities, as well as the ability to inhibit cholesterol absorption from the intestine and synthesis in the liver. The seed is used as a diuretic, emollient, and a tonic for the liver and kidneys [35]. Sesame lignans such as sesamin, episesamin, sesamolin, and γ-tocopherol isolated from Sesamum indicum and Sesamum radiatum seeds among other species have been implicated as having estrogenic and/or anti-estrogenic [36] and antioxidant [36] properties.…”
Section: Discussionmentioning
confidence: 99%
“…Sesame seed is not only a good source of edible nutrients, but is also widely considered to have medicinal value that includes antioxidant, anti-ageing, antimutagenic, antihypertensive, and anti-inflammatory activities, as well as the ability to inhibit cholesterol absorption from the intestine and synthesis in the liver. The seed is used as a diuretic, emollient, and a tonic for the liver and kidneys [35]. Sesame lignans such as sesamin, episesamin, sesamolin, and γ-tocopherol isolated from Sesamum indicum and Sesamum radiatum seeds among other species have been implicated as having estrogenic and/or anti-estrogenic [36] and antioxidant [36] properties.…”
Section: Discussionmentioning
confidence: 99%
“…), a member of the Pedaliaceae family, is an important oilseed crop widely cultivated in tropical and subtropical areas and highly drought‐tolerant soils, and thus it is well‐suited for different crop rotation practices . The sesame plant is popularly used as a herbal remedy due to its antioxidant, anti‐aging, antimutagenic, antihypertensive, and anti‐inflammatory effects, as well as its ability to inhibit cholesterol absorption from the intestine and synthesis in the liver . This plant is also an important source of edible oil due to its high essential fatty acid content (ω‐3 and ω‐6), sterols, tocopherols, and tocotrienols .…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Previous studies have shown that SI possesses hepatoprotective, hypoglycemic, antihypertensive, antitumorigenic, and anti-estrogenic properties as well as its ability to increase Vitamin E concentration without the use of Vitamin E supplements and its beneficial effect in treating Parkinson's disease. [ 11 12 ] It has been reported recently to contain free radical scavengers such as flavonoids, saponins, tannins, and phenolic compounds in appreciable quantities. [ 11 ]…”
Section: Introductionmentioning
confidence: 99%